2012
DOI: 10.1088/0957-0233/23/6/065604
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mechanical and geometrical properties of embedded long-gauge strain sensors on the accuracy of strain measurement

Abstract: In many civil and geotechnical applications it is of interest to monitor the strain deep inside the structure; consequently, it is necessary to embed the sensors into the structure's material. Construction and geotechnical materials, such as concrete and soil, can be affected by local defects, e.g. cracks, air pockets and inclusions. To monitor these materials at a structural level it is necessary to use long-gauge sensors. As the sensor has to be embedded in the host material, its presence causes perturbation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…According to the literature, many stress transfer models have been established to describe the interaction between the embedded optical fiber and the surrounding medium, together with a few numerical analyses studies (e.g. [24][25][26][27][28][29][30][31][32][33]). However, these interface models cannot take into account the effects of confining pressure, which is a crucial factor for soil inclusions [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, many stress transfer models have been established to describe the interaction between the embedded optical fiber and the surrounding medium, together with a few numerical analyses studies (e.g. [24][25][26][27][28][29][30][31][32][33]). However, these interface models cannot take into account the effects of confining pressure, which is a crucial factor for soil inclusions [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the sensor orientation could change the strain transfer rate from 0.90 to 0.92. Strain transfer behaviors of long‐gauge FBG sensors and distributed sensors were quantitatively studied and implemented in condition monitoring . In the last decade, the strain transfer rate of fiber optic sensors in asphalt pavements has been intensively investigated by Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of these designs, the embedded FBG sensors packaged by steel tube or capillary are widely used for the reason that steel tube can be well matched with concrete material. Many researchers also studied strain transfer mechanism and sensing properties of encapsulated FBG sensors . Experiment results show that the strain sensing properties of encapsulated FBG sensor are nearly the same as that of bare FBG.…”
Section: Introductionmentioning
confidence: 99%